Representation of Traditional Culinary of Central Java in The Explainer Video of The Youtube Account of The Central Java Language Centre As An Alternative Teaching Material For BIPA - Firdia Rias Tiyaningsih, Fatma; Restu Aulia, Hanindya (International Proceedings of Nusantara Raya, 2023)
This article aims to describe the representation of traditional Central Java culinary in the explainer video of the Central Java Language Center youtube account and describe the utilisation of the analysis results as an alternative BIPA teaching material. The research method used is descriptive qualitative. This research uses data collection techniques, namely listening and recording techniques. The data were analysed using Miles and Huberman's interactive analysis technique. The results of the study are the benefits of traditional Central Java culinary in the explainer video of the Central Java Language Centre youtube account as a result of analysis as an alternative BIPA teaching material. Culinary includes an identity symbol of one of Indonesia's cultural heritages that needs to be preserved.